Effect of parathyroid hormone-related protein in an in vitro hypertrophy model for mesenchymal stem cell chondrogenesis - Mueller, Michael B. (Springer-Verlag, 2013)
PURPOSE: Mesenchymal stem cells (MSCs) express markers of hypertrophic chondrocytes during chondrogenic differentiation. We tested the suitability of parathyroid hormone-related protein (PTHrP), a regulator of chondrocyte hypertrophy in embryonic cartilage development, for the suppression of hypertrophy in an in vitro hypertrophy model of chondrifying MSCs. METHODS: Chondrogenesis was induced in human MSCs in pellet culture for two weeks and for an additional two weeks cultures were either maintained in standard chondrogenic medium or transferred to a hypertrophy-enhancing medium. PTHrP(1–40) was added to the medium throughout the culture period at concentrations from 1 to 1,000 pM. Pellets were harvested on days one, 14 and 28 for biochemical and histological analysis. RESULTS: Hypertrophic medium clearly enhanced the hypertrophic phenotype, with increased cell size, and strong alkaline phosphatase (ALP) and type X collagen staining. In chondrogenic medium, 1–100 pM PTHrP(1–40) did not inhibit chondrogenic differentiation, whereas 1,000 pM PTHrP(1–40) significantly reduced chondrogenesis. ALP activity was dose-dependently reduced by PTHrP(1–40) at 10–1,000 pM in chondrogenic conditions. Under hypertrophy-enhancing conditions, PTHrP(1–40) did not inhibit the induction of the hypertrophy. At the highest concentration (1,000 pM) in the hypertrophic group, aggregates were partially dedifferentiated and differentiated areas of these aggregates maintained their hypertrophic appearance. CONCLUSIONS: PTHrP(1–40) treatment dose-dependently reduced ALP expression in MSC pellets cultured under standard chondrogenic conditions and is thus beneficial for the maintenance of the chondrogenic phenotype in this medium condition. When cultured under hypertrophy-enhancing conditions, PTHrP(1–40) could not diminish the induced enhancement of hypertrophy in the MSC pellets.